2021
DOI: 10.1177/24730114211061405
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes Between Suture Button Technique and Screw Fixation Technique in Patients With Acute Syndesmotic Diastasis: A Meta-analysis of Randomized Controlled Trials

Abstract: Background: Our aim was to compare the outcome between suture button (SB) stabilization and syndesmotic screw fixation (SF) in patients with acute syndesmotic diastasis. Methods: A systematic literature search up to June 30, 2021, was performed to identify randomized controlled trials (RCTs) comparing outcomes of SB with SF techniques in patients with acute syndesmotic diastasis. We calculated mean differences for continuous outcomes, using the Hartung-Knapp-Sidik-Jonkman method, and odds ratio for dichotomous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
6

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 74 publications
0
10
0
6
Order By: Relevance
“…A search of PROSPERO identified only 1 registered review on the topic in the last 2 years, which has subsequently been published by Ramadanov et al 21 This paper has significant methodological flaws, as it only searched PubMed and Google Scholar. The presence of additional papers found from an unclear and non-reproducible Google Scholar search brings into question whether the entire body of literature was included, given that only 1 database was searched.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A search of PROSPERO identified only 1 registered review on the topic in the last 2 years, which has subsequently been published by Ramadanov et al 21 This paper has significant methodological flaws, as it only searched PubMed and Google Scholar. The presence of additional papers found from an unclear and non-reproducible Google Scholar search brings into question whether the entire body of literature was included, given that only 1 database was searched.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 12 systematic reviews examining clinical outcomes published between July 2017 and December 2021 was found, and these are summarized in Table 1. [14][15][16][17][18][19][20][21][22][23][24][25] Systematic reviews of biomechanical studies and cost analysis were not included. Five of the 12 reviews were limited solely to RCTs, while the remaining 7 included quasi-experimental and retrospective studies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations